Synthesis and photoluminescence properties of novel core–shell–shell SiO2@CePO4:Tb@SiO2 submicro-spheres. Issue 40 (26th September 2018) - Yang, Kui-Suo; Li, Yi-Lian; Ma, Yang-Yang; Feng, Li-Na; Wu, An-Ping; Qiao, Yan; Bao, Jin-Rong; Li, Wen-Xian; Zhu, Xiao-Wei; Yu, Ran-Bo
Abstract : The low-cost preparation of the core–shell–shell SiO2 @CePO4 :Tb@SiO2 was achieved, and the biocompatibility was improved with the use of SiO2 . Abstract : A novel core–shell–shell SiO2 @CePO4 :Tb@SiO2 submicro-sphere was controllably synthesized by a bridging ligand organosilane HOOCC6 H4 N(CONH(CH2 )3 Si(OCH2 CH3 )3 )2 (MABA-Si) connecting the silica core and rare earth ions. The as-synthesized samples were investigated using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and infrared spectroscopy (IR). It is found that SiO2 @CePO4 :Tb@SiO2 has a ∼25 nm outermost shell, a ∼4 nm intermediate shell, and a ∼200 nm core. SiO2 @CePO4 :Tb@SiO2 exhibits stable photoluminescence properties in aqueous solution: its photoluminescence intensity was unquenched even after 15 days. The core–shell–shell submicro-spheres were found to have better photoluminescence than the core–shell submicro-spheres because the SiO2 shell protected the phosphor materials and then improved its photoluminescence intensity and biocompatibility. A formation mechanism of the core–shell–shell SiO2 @CePO4 :Tb@SiO2 submicro-spheres was proposed. Thus, the low-cost preparation of the core–shell–shell SiO2 @CePO4 :Tb@SiO2 submicro-spheres could be rationally achieved using SiO2 .